The Effects of Monetary Easing on Spatial Convergence in Hungary - Kocziszky, György; Szendi, Dóra (Theory, Methodology, Practice – Review of Business and Management, 2015)
There has been no substantive change in the existing disparities between the central and peripheral regions in the ten years after the Hungarian accession to the EU (2004-2014). The authors summarise in their study the possibility of econometric modelling of the relationship between regional convergence and monetary easing. On the basis of the represented model the effects of monetary easing, beginning in 2012, on the central, peripheral and semi-peripheral territories are construed, and other interventions needed to reach substantive path-correction are identified.